Development of the small scale piston type briquetting tool - Mohammad Khairulnizam, Ibrahim (2013)
Currently, renewable energy is becoming an important source of energy in our world. Renewable energy is a solution that can overcome the problems that occur in our world right now such as global warming, urban smog, acid rain and many more dangerous emmisions. Biomass is one the sources of renewable energy that have specific properties that can change our world environment right now. Biomass use and application is the one way for decreasing the above negative effect to the world. Briquette technology is the one technology which uses the biomass product in the right way. In order to develop a small scale of piston type briquetting tools, an analysis was carried out to choose the best design to develop briquette machine. Four samples of different designs then was sketch in 3D drawing by using Solidworks Premium Software. Every designs was sketch in different application of theories which are pascal theory, bottle jack theory, bottle jack theory with heavy duty spring and use of power supply of motor. By using Solidwork Premium Software stress strain anlysis, the designs then being analysed. After do the analysis, comparison and concept selection between the designs was carried out. The result is finalised and the concept of using of power supply of motor is selected. For the final stage, the machine was fabricate by using the selected concept.